The power performance of an offshore floating wind turbine in platform pitching motion - Wen, Binrong; Dong, Xingjian; Tian, Xinliang; Peng, Zhike; Zhang, Wenming; Wei, Kexiang (Energy (Oxford), 2018)
The platform pitching motion of the Offshore Floating Wind Turbine (OFWT) introduces an additional wind profile to the rotor, which may significantly impact the power performance of the OFWT. In this paper, the power performance of an OFWT in platform pitching motion is investigated using the Free Vortex Method (FVM). Firstly, the pitching and non-pitching cases are compared. Then, the power performance of the OFWT in pitching motions with different amplitudes and frequencies is investigated at the design point (tip speed ratio λ = 7). Afterwards, the reduced frequency k is proposed to integrate the influences of the platform pitching amplitude and frequency. The power performance curves of the pitching OFWT are derived as functions of λ and k in the whole operating region. Results show that as k increases, the mean power output decreases at low λ but increases at high λ. The mean power coefficient declines with the increase of k. The power variation increases with the increases of λ and k. To make up the loss of the mean power coefficient and to mitigate the side effects resulted from the power variation, advanced control strategies and platforms with good motion performances should be developed for OFWTs. •The Free Vortex Method is used to study the power performance of a pitching OFWT.•The reduced frequency is introduced as an independent variable of power performance.•Impact of the reduced frequency on mean power output varies with the tip speed ratio.•The power variation increases with the tip speed ratio and the reduced frequency.•Novel controllers and more stabilized platforms should be developed for OFWTs.